Pengaruh Media Chromebook terhadap Kemampuan bernalar Kritis dan Pemahaman Struktur Bumi siswa kelas 5 - Nurhalima; Kusmiyati (Yayasan Citra Dharma Cindekia, 2024)
This article discusses the impact of Chromebook media on critical reasoning skills and understanding of Earth's structure among 5th-grade students. Education that focuses on enhancing students' critical reasoning and comprehension has become a crucial aspect in preparing a smart and creative generation. Teachers can adapt teaching methods to meet students' needs, interests, and abilities. By utilizing various Chromebook media tools, teachers can provide broad access to information to support collaboration. This study aims to determine the influence of Chromebook-based learning media on critical reasoning skills and understanding of Earth's structure concepts among 5th-grade students. The results indicate that students using Chromebooks showed significant improvements in critical reasoning skills and comprehension of Earth's structure concepts compared to the group using conventional media. By using quantitative research methods through a pretest-posttest design, students using Chromebook media were compared to those using conventional media. Thus, this study concludes that Chromebooks play an essential role in facilitating a learning process that supports students' critical thinking skill development.